Theorising Development in Africa : Towards Building an African Framework of Development - Mawere, Munyaradzi (Book collections on Project MUSE., 2017)
How come Africa is so underdeveloped when it is one of the richest continents on earth? Indeed, Africa is a paradox: it is poor and rich at the same time! Resource-wise, Africa is among the top richest continents in the world, yet development-wise it is the poorest of all continents. This paradox desperately needs comprehensive theoretical unpacking and rethinking if Africa is to achieve breakthroughs to the multifaceted development-related problems that have haunted it since the beginning of its unequal encounters with Europe. Regrettably, current Eurocentric development theories fall short on several fronts. The need for a comprehensive body of knowledge -- theories and models -- from the perspective of Africans persists in urgency. The present volume is an attempt to theorise Africa's [under-]development with a view to provide a sustainable enduring framework of operations that will arrest the elusive predicament of the continent while taking it forward from its current position of passivity. It rethinks and re-imagines a number of externally imposed problematic mechanisms used (un-)consciously in Africa, with the intention to raise awareness and foster critical thinking in scholars and scholarship on African development. With its predicament-oriented theorising, the book is a pacesetter on how to think and research Africa's [under-]development. It is also an invaluable asset for social scientists, policy makers, development practitioners, civil society activists and politicians.